Consumer Perception Of Shopping Center Branding And Its Role In Shopping Center Choice - Mohd Idris, Aida Syukrena (2002)
This paper attempts to find out what consumers think of shopping center branding. It set the scene by describing the situation in the local Malaysian shopping center industry. Despite the slow pace in the local industry due to the current economic climate, developers are still building more new centers which could lead to more problems such as over -storing of retail space and threatened survival of retailers, which could have an adverse effect on shopping centers as they are highly tenant-dependent. So how can a shopping center overcome this problem? One way is through branding.